Sosialisasi Pendirian Bank Sampah Soka Resik Bagi Peningkatan Pendapatan dan Pemberdayaan Perempuan di Ciwuni - Anisha Dian Iswahyuni; Frida Amriyati Azzizzah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Waste is one of society's main problems in environmental management which until now does not have an appropriate handling solution. This is due to the community's habit of still implementing collection, transport and disposal in waste management, as well as the unavailability of suitable locations in each village that can be used as waste management sites. This waste problem is also experienced by residents of Sokawera Hamlet, Ciwuni Village, Kesugihan District. The waste produced by residents is usually collected and then burned. This waste management problem must be addressed immediately because it can affect the quality of life and the quality of the village environment. The effort taken is not to provide or create a waste disposal area, but rather to invite the public to start caring and being aware of the importance of managing waste wisely and correctly. This community empowerment activity is carried out by holding outreach and establishing a waste bank to change people's mindset about waste, mentoring, comparative studies, and establishing a Waste Bank to manage waste so that it can have economic value. With the formation of the Soka Resik waste bank, it is hoped that in the future it will become the spearhead in waste management.